Genetic Variability, Correlation and Path Analysis of Floral, Yield and its Component Traits of Maintainer Lines of Rice (Oryza sativa L.) (Bangladesh Rice Journal, 2021)
Direct selection based on crop yields is paradox in breeding programmes because of its complex polygenically inherited character, which is influenced by its component traits. A field experiment was conducted to establish the extent of association between yield and yield components and other characters in maintainer lines of rice. Analysis of variance revealed that significant amount of genetic variability was present in the entire characters studied except grain length, grain width and flag leaf breadth. High heritability coupled with high genetic advance as percent of mean was observed for number of tillers per hill, number of panicles per plant, number of grains per panicle, 1000-grain weight (TGW), filled grains per panicle, flag leaf length, stigma breadth, filament length suggesting preponderance of additive gene action in the expression of these characters. The correlation coefficient between grain yield per plant and other quantitative characters attributing to yield showed that grain yield was significantly and positively associated with number of grains per panicle, TGW, spikelet fertility, filament length and pollen fertility at both genotypic and phenotypic levels. Path coefficient at genotypic level revealed that panicle length, number of effective tillers/plant, number of grains per panicle, TGW, filled grains per panicle, spikelet fertility, stigma length, stigma breadth, filament length and pollen fertility had direct positive effect on grain yield indicating importance of these parameters as the main contributors to yield. Thus, a genotype with higher extent of these traits could be selected as parents from existing genotypes for genetic improvement of yield in hybrid rice.Bangladesh Rice J. 24 (1): 1-9, 2020